2018
DOI: 10.1161/jaha.118.008918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipid‐Lowering and Antihypertensive Treatments in Addition to Healthy Lifestyles in Primary Prevention: An Analysis of the HOPE‐3 Trial

Abstract: BackgroundIt is not clear whether the effects of lipid‐lowering or antihypertensive medications are influenced by adherence to healthy lifestyle factors. We assessed the effects of both drug interventions in subgroups by the number of healthy lifestyle factors in participants in the HOPE‐3 (Heart Outcomes Prevention Evaluation) trial.Methods and ResultsIn this primary prevention trial, 4 healthy lifestyle factors (nonsmoking status, physical activity, optimal body weight, and healthy diet) were recorded in 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The impact of adherence or otherwise to a healthy lifestyle has not been addressed in this analysis. Such an analysis in the entire HOPE 3 study population 12 assessed the effect of drug interactions in subgroups by adherence to two or more of four healthy lifestyle factors – (non-smoking (never smokers and those who had quit more than a year earlier) versus current smoking; moderate or vigorous physical activities versus less activity; optimal waist/hip ratio (≤0.89 for men and ≤0.84 for women) versus a higher ratio and a healthy versus unhealthy diet, assessed using a 9-point Mediterranean diet score) with those with less than two. This analysis reported that those who had two or more of these factors had overall lower rates of cardiovascular events (HR 0.85, 95% CI 0.73–1.00).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of adherence or otherwise to a healthy lifestyle has not been addressed in this analysis. Such an analysis in the entire HOPE 3 study population 12 assessed the effect of drug interactions in subgroups by adherence to two or more of four healthy lifestyle factors – (non-smoking (never smokers and those who had quit more than a year earlier) versus current smoking; moderate or vigorous physical activities versus less activity; optimal waist/hip ratio (≤0.89 for men and ≤0.84 for women) versus a higher ratio and a healthy versus unhealthy diet, assessed using a 9-point Mediterranean diet score) with those with less than two. This analysis reported that those who had two or more of these factors had overall lower rates of cardiovascular events (HR 0.85, 95% CI 0.73–1.00).…”
Section: Discussionmentioning
confidence: 99%